A systematic review of phase-II trials of thalidomide monotherapy in patients with relapsed or refractory multiple myeloma - Glasmacher, Axel; Hahn, Corinna; Hoffmann, Florian; Naumann, Ralph; Goldschmidt, Hartmut; Lilienfeld-Toal, Marie von; Orlopp, Katjana; Schmidt-Wolf, Ingo; Gorschlüter, Marcus (British journal of haematology, 2006)
The activity of thalidomide in relapsed or refractory multiple myeloma is widely accepted but not yet demonstrated in a randomised-controlled trial. A systematic review of the published clinical trials of these patients could reduce the possible bias of single phase-II studies. A systematic search identified 42 communications reporting on 1674 patients. Thirty-two trials used an escalating dosing regimen and four a fixed dose regimen (one dose with 50 mg/d, three doses with 200 mg/d). The target dose in the dose escalating trials was 800 mg/d in 17 trials, 400-600 mg/d in 10 and 200 mg/d in one trial. The intention-to-treat population for efficacy was 1629 patients with a median age of 62 years. The complete and partial (>50% reduction in monoclonal protein) response rate was 29·4% (95%-confidence interval, 27-32%). The rates for minor responses or stable disease were 13·8% (12-16%) and 11·0% (9-13%). Progressive disease was reported in 9·9% (8-11%). The median overall survival from all trials was reported at 14 months. Severe adverse events (grade III-IV) included somnolence 11%, constipation 16%, neuropathy 6%, rash 3%, thrombo-embolism 3%, cardiac 2%. In conclusion, thalidomide monotherapy achieved complete and partial responses in 29·4% of patients with relapsed or refractory multiple myeloma.